Reconstruction of Legal Arrangements Concerning the Influence of Political Parties on the Independence of Members of the Regional People's Representative Council in the Indonesian Constitutional System - Marsanova Andesra; Ahmad Redi (Journal Customary Law, 2026)
This study aims to analyze and reconstruct the legal regulations regarding the influence of political parties on the independence of DPRD members in the Indonesian constitutional system. Using normative juridical methods through legislative and conceptual approaches, this study found that although the principle of popular sovereignty in the 1945 Constitution of the Republic of Indonesia places the DPRD as an independent representation of the people, in practice there is dominance of political parties through the mechanisms of factions, party discipline, and Interim Replacement as regulated in Law Number 17 of 2014 concerning the MPR DPR DPD and DPRD and Law Number 2 of 2011 concerning Political Parties. This condition indicates a tendency for a hidden imperative mandate that weakens the independence of DPRD members and impacts the quality of regional democracy. Therefore, it is necessary to reconstruct legal regulations that emphasize the principle of a free mandate, limit political party intervention, and strengthen legal protection for the independence of DPRD members in order to realize substantive representative democracy.